N-Isobutyloxycarbonylation for improved detection of 3 '-hydroxystanozolol and its 17-epimer in doping control - Choi, MH; Chung, BC (ROYAL SOC CHEMISTRY, 2001)
An improved screening method was developed for 3'-hydroxystanozolol and its 17-epimer in human urine involving gas chromatography-mass spectrometry (GC-MS) with N-isobutyloxycarbonyl (isoBOC) and O-trimethylsilyl (TMS) derivatization. A procedure was reported previously for the pentane extraction of many steroids from urine in doping control, but it was not suitable for the detection of stanozolol metabolites. Compared with the n-pentane extraction method, which gave a poor recovery (< 10%), isoBOC extraction resulted in a good recovery (> 80%). The sensitivity and specificity of mixed N-isoBOC-O-TMS derivatization were adequate for the detection of 3'-hydroxystanozolol and its 17-epimer when 3 ml of urine was used with spiking at a level of 2 ng ml(-1). When applied to a stanozolol-positive urine sample, the proposed method allowed rapid and sensitive screening for the detection of 3'-hydroxystanozolol and its 17-epimer.
Keywords: CHROMATOGRAPHY-MASS-SPECTROMETRY; ANABOLIC-STEROID METABOLITES; URINARY METABOLITES; IDENTIFICATION; STANOZOLOL; HAIR